Oral Health in Dementia-A Review - Sudakshina Mukherjee, E.Rajesh, N2 , Aravindha Babu3 , L.Malathi4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dementia is a neurodegenerative disorder affecting the cognitive and motor skill of the patients. It can bereversible and irreversible. People with dementia lose their ability to do basic procedures to maintain oralhygiene thus poor oral hygiene and its associated oral diseases are not an uncommon findings in thesepatients. In this review we will be discussing about various oral conditions faced by these patients.